2016
DOI: 10.1177/1558944716661995
|View full text |Cite
|
Sign up to set email alerts
|

Improved Surgical Outcomes With Endoscopic Carpal Tunnel Release in Patients With Severe Median Neuropathy

Abstract: ECTR is a safe and effective alternative to OCTR for patients with severe CTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
(30 reference statements)
0
5
0
1
Order By: Relevance
“…Endoscopic techniques are attractive given that the previous studies have demonstrated no significant difference in outcomes between open and endoscopic approaches; endoscopic techniques provide visualization of the entire transverse carpal ligament without requiring the second incision in the palm, and minimally invasive/endoscopic approaches are increasingly desired by patients. 19,20 Badia et al 21 was the first to propose an endoscopic technique; however, their approach used 2 distinct incisions (an extensive FCR approach for fracture fixation and a separate small transverse approach for endoscopic neurolysis). Low and Cheah 9 published a technical note on the possibility of endoscopic carpal tunnel release using the Henry approach; however, the feasibility and results in a clinical setting were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic techniques are attractive given that the previous studies have demonstrated no significant difference in outcomes between open and endoscopic approaches; endoscopic techniques provide visualization of the entire transverse carpal ligament without requiring the second incision in the palm, and minimally invasive/endoscopic approaches are increasingly desired by patients. 19,20 Badia et al 21 was the first to propose an endoscopic technique; however, their approach used 2 distinct incisions (an extensive FCR approach for fracture fixation and a separate small transverse approach for endoscopic neurolysis). Low and Cheah 9 published a technical note on the possibility of endoscopic carpal tunnel release using the Henry approach; however, the feasibility and results in a clinical setting were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the surgical method utilized is also a risk factor. Some studies have found recurrence rates to be between 2.6-7% following endoscopic carpal tunnel surgery, which has lately become more popular [15,16]. The complaint of numbness was found to have continued for longer in cases who underwent endoscopic surgery [17].…”
Section: Discussionmentioning
confidence: 99%
“…Calotta et al 16 included 126 patients. 39 patients were managed with Endoscopic release carpal tunnel syndrome and 99 open methods.…”
Section: Akkurt Et Al Reported Both Endoscopic and Openmentioning
confidence: 99%